Implementation Of Rocket Stove As An Environmentally Friendly Waste Management Innovation In The Green Village Program Of Cibaregbeg Village - M. Sigit Adi Nugraha; Enden Suryati; Tanto Heryanto (Universitas INABA, 2025)
This community service project addresses the critical issue of improper waste management in Cibaregbeg Village, where open burning remains a widespread practice due to the lack of a formal waste collection system. The program introduces Rocket Stove technology as an environmentally friendly innovation that enables more efficient, smoke-reduced combustion of household waste. Implementation methods include environmental education, collaborative construction, training on operation procedures, and integration within the Green Village initiative. The results demonstrate improved community awareness, reduced waste accumulation, and noticeable improvements in environmental quality. Overall, the Rocket Stove initiative proves to be sustainable, and scalable solution for rural waste management.